Acoustic and temporal parameters in malayam speakers using different types of t.e.p. prosthesis - Sunitha M (Journal of All India Institute of Speech and Hearing, 1970)
Rehabilitation of a laryngectomee aims at restoring the pre-operative condition of the patient as far as possible in terms of psychological,physiological, social and economic status i.e. basically by restoring voice. This is achieved by the efficiency of the patient in making use of his remaining structures for speaking.